2018
DOI: 10.1111/joa.12924
|View full text |Cite
|
Sign up to set email alerts
|

Physiological in vitro sacroiliac joint motion: a study on three‐dimensional posterior pelvic ring kinematics

Abstract: The sacroiliac joint (SIJ) is a well-known source of low back and pelvic pain, of increasing interest for both conservative and surgical treatment. Alterations in the kinematics of the pelvis have been hypothesized as a major cause of SIJ-related pain. However, definitions of both the range and the extent of physiological movement are controversial, and there are no clear baseline data for pathological alterations. The present study combined a novel biomechanical setup allowing for physiological motion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 75 publications
(181 reference statements)
4
35
0
Order By: Relevance
“…Iliac rotation relative to the sacrum was later named nutation and counter-nutation 19 , thought ambiguity exists as nutation was also named the combined rotation and translation movement of the sacrum relative to both innominate bones 27 . The above studies 4 , 11 , 28 30 have reported that the sacrum rotates approximately 2° on the sagittal plane, which seems to indicate such movement. Bruna-Rosso et al have shown the rotation of the sacrum with vector diagrams in FEM 24 .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Iliac rotation relative to the sacrum was later named nutation and counter-nutation 19 , thought ambiguity exists as nutation was also named the combined rotation and translation movement of the sacrum relative to both innominate bones 27 . The above studies 4 , 11 , 28 30 have reported that the sacrum rotates approximately 2° on the sagittal plane, which seems to indicate such movement. Bruna-Rosso et al have shown the rotation of the sacrum with vector diagrams in FEM 24 .…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the SIJ had small motion of less than 1 mm, and moved separately on the left and right SIJ. The range of the SIJ movements has been investigated with various methods; on patients with SIJ disorders 0.7 mm by Sturesson et al 4 , 0.7 mm by Jacob and Kissling 28 , and 0.3 mm by Sturesson et al 29 , on healthy individuals 0.47 mm by Kibsgård et al 30 , on cadavers 0.8 mm by Miller et al 31 , less than 1 mm by Takayama 5 and 0.3 mm by Hammer et al 11 , and on FEM 0.3 mm by Bruna-Rosso et al 24 . Our study showed that displacement of SIJ cartilage was ranged from 0.3 to 0.6 mm, which was similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, loads are applied in only one direction of motion [4,5]. These movements are often measured on the surface of the specimen using only few tactile displacement meters [4] or glued-on markers [2]. The underlying soft tissue can induce inaccuracies of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Further improvement of implant fixation requires knowledge about the load transfer from the spine to the hip region, which is, therefore, a major field of biomechanical investigation. However, studies in the literature usually investigated only single directional loadcases [2,4]. To deepen our understanding how these components interact during load transfer, the current study aims for identification the kinematics of the interacting bone segments under different loading conditions.…”
Section: Introductionmentioning
confidence: 99%